(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Therapeutic plasma exchange (TPE) is a procedure used in neurological disorders where autoimmunity plays a major role. Though it is a relatively safe procedure, severe complications may occur. Objective: The aim of the present study was to analyze the incidence of TPE related complications in patients with different neurological disorders. Methodology: This prospective study was conducted in 91 patients, in department of Transfusion Medicine at National Institute of Neurosciences and Hospital (NINS) from February 2014 to January 2017 for a period of three (03) years. All admitted patients with neurological disorders advised for TPE were included in this study. Results: Age range was from 13 to 70 years with a mean age of 37.14±13.79 years. 67(74%) were men and 24(26.0%) were women. The most common diagnosis was Guillain-Barré Syndrome (GBS) in 79.1 % (n=72) cases followed by myasthenia gravis (MG) in 13.2% (n=12), chronic inflammatory demyelinating polyneuropathy (CIDP) in 6.6 % (n= 6), multifocal motor neuropathy (MMN) in 1.1% (n=1) cases. Total number of 332 TPE sessions was performed with the median of 4 sessions per patient (range 1 to 9). Total 99 (29.8%) adverse reactions occurred in 332 TPE sessions. The most common adverse effect was hypotension (n=35, 10.54 %) followed by allergic reactions (n=29, 8.73 %), access problem (n= 12, 3.61 %) and vomiting (n=8, 2.41 %). Most of the adverse reactions were mild and improved spontaneously or by using simple medications. Out of 332 TPE sessions, 330(99.4%) procedures were completed successfully after managing the adverse reactions. TPE were discontinued in 2 occasions (0.6% of procedures) due to inadequate venous access. There was no mortality related to TPE procedure. Conclusion: In spite of few complications, TPE can be considered as a safe method of treatment in neurologic disorders when carried out with all necessary precautions. Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 69-74